Voice hoarseness in a patient with underlying Eisenmenger’s syndrome: a case report - Palak Suryavanshi; Sreejit Parameswaran; Nishant Sharma; Russell A. Murphy; Anil R. Sharma (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The natural history of patients diagnosed with Eisenmenger’s Syndrome typically revolve around the pediatric population. Medical advances have allowed these patients to live longer and present with a different subset of symptoms as a result of the progression of their disease process. Case presentation In this case report, we discuss a 77-year-old Caucasian female with Eisenmenger’s Syndrome presenting with hoarseness. Clinical and imaging studies reveal a left vocal cord paralysis secondary to a progressively enlarging patent ductus arteriosus (PDA) and dilation of pulmonary arteries causing mass effect on the left recurrent laryngeal nerve. Conclusion From a clinical perspective, this case highlights the need for otolaryngologists to be aware of the pathophysiology of Eisenmenger’s Syndrome as it progresses with age.